Systemic and participatory diagnosis of Médio Maracá (AP) communities: preparing for alternative electirc energy integration in "Light for all" program (Gestão & Regionalidade, 2015)
Facing the challenge of universalization of electricity, the government demonstrates interest in taking over the responsibility to invest in technologies that allow the generation of electricity in isolated communities and simultaneously prepare them to use energy productively. This study, the result of studies of Médio Maracá communities of Extractive Settlement Project (PAE) of Maracá in the city of Mazagão, in the state of Amapá, presents the methodology of Systemic Management and Participatory Local (GSPL), which was formulated to support the community in local management process from the insertion of energy. The main objective is to demonstrate the results of the analysis made in the community and point out the necessary actions to: a) produce goods and services that improve the quality of life of local population, particularly of their family income, b) maintaining the operation of technology supply and c) the use of energy in activities for social development. For the diagnosis were performed literature on work in the community, interviews and questionnaires to community residents.